Understanding psychology students’ perspective on video psychotherapy and their intention to offer it after graduation: a mixed-methods study - Meier, Jennifer Virginie; Noel, Josephine Alexandra; Kaspar, Kai (Frontiers in Psychology, 2023)
Video psychotherapy (VPT) demonstrated strong clinical efficacy in the past, with patients and psychotherapists expressing satisfaction with its outcomes. Despite this, VPT only gained full recognition from the German healthcare system during the COVID-19 pandemic. As society increasingly relies on new media, it seems likely that VPT will become even more relevant. Previous studies surveyed practicing psychotherapists and patients about advantages and disadvantages of VPT. In contrast, our approach targets a younger generation, specifically psychology students intending to become licensed practitioners after graduation. This view on VPT and its potential for future implementation brings a unique perspective to the topic from a new generation that has grown up with digital media. The mixed-methods study, conducted in an online survey format, had two main objectives. Firstly, we investigated which person-related variables are associated with psychology students’ behavioral intention to offer VPT after graduation. With a sample of 255 psychology students, a multiple regression model explained 73% of inter-individual variance, with attitudes towards VPT showing the strongest relationship with intention to offer VPT. The second objective was to explore psychology students’ perceptions of advantages and disadvantages of VPT and identified their desired learning opportunities regarding VPT in their study program. Therefore, we analyzed 2314 student statements using qualitative content analysis and developed a category system accordingly. In terms of advantages, the most frequently mentioned categories were low inhibition threshold, flexibility in terms of location, and no travel necessary. For disadvantages, the predominant categories included lack of closeness between patient and psychotherapist, lack of nonverbal cues, and problems with technology or internet connection. Our research revealed significant congruence between the advantages and disadvantages identified in our study and those reported by practicing psychotherapists. Regarding desired learning opportunities, training for technical skills, practical application through role-playing and self-experience, and general information about VPT were the most mentioned categories. Furthermore, we identified numerous additional aspects related to these topics. The results and limitations of the study are discussed, addressing their theoretical and practical implications for the training of future psychotherapists, along with the provision of a five-step plan.